2019
DOI: 10.3390/medicina55060244
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Among Lebanese Pregnant Women Toward Cord Blood Stem Cell Storage and Donation

Abstract: Background: Umbilical cord blood (UCB) used to be considered waste material and was discarded at birth. However, cord blood is now considered a rich source of adult stem cells that can be used to treat many conditions and diseases. This study was performed to determine pregnant women’s knowledge and attitudes toward cord blood stem cell banking and donation in Lebanon. Methods: A descriptive study was conducted in antenatal clinics in Beirut and data were collected using a questionnaire distributed to pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
2
3
0
3
Order By: Relevance
“…The authors showed that more than three-quarters of pregnant women declare having a poor knowledge of UCB (Katz et al 2011 ). Similar results were seen in a study conducted in Greece, where only 48% of the participants had a full knowledge about UCB donation and storage (Karagiorgou et al 2014 ), in a study performed in Beirut more than half of the women reported no prior knowledge (Saleh 2019 ).…”
Section: Discussionsupporting
confidence: 81%
“…The authors showed that more than three-quarters of pregnant women declare having a poor knowledge of UCB (Katz et al 2011 ). Similar results were seen in a study conducted in Greece, where only 48% of the participants had a full knowledge about UCB donation and storage (Karagiorgou et al 2014 ), in a study performed in Beirut more than half of the women reported no prior knowledge (Saleh 2019 ).…”
Section: Discussionsupporting
confidence: 81%
“…Kordon kanı ile tedavi konusundaki araştırmaların gün geçtikçe artması ve klinik uygulamalara dahil edilmesi konunun önemini açıkça ortaya koymaktadır [25][26][27] . Literatür incelendiğinde; kordon kanı bankacılığı ile ilgili bireylere yapılacak doğru bilgilendirmenin alınacak kararları doğrudan etkileyebileceği bildirilmektedir [20][21][22] . Bu bağlamda çalışmada, sağlık profesyoneli adayı olan ve ileride kordon kanı ve bankacılığına ilişkin eğitim ve danışmanlık yapması beklenen hemşirelik öğrencilerinin kordon kanı ve bankacılığına ilişkin düşünceleri saptanmıştır.…”
Section: Discussionunclassified
“…Öğrencilerin medyada yer alan her bilginin doğru olmayabileceği ve bilimsel bilgiye nasıl ulaşabilecekleri konusunda bilinçlendirilmeleri önemlidir. Literatürde yer alan konuya ilişkin toplum temelli çalışmalarda da bu konudaki bilgi eksikliğine dikkat çekilerek bilgi kaynaklarının çoğunlukla medya olduğu, daha az çalışmada ise sağlık personeli olduğu belirtilmektedir 10,20,22,23,[28][29][30][31] . Sağlık personellerinin etkin danışmanlık yapabilmesi için kendi bilgilerinin yeterli olması gereklidir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…After conducting an extensive literature review of published studies regarding CBB in the last 10 years, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] the investigators developed a 29-item survey examining sociodemographic factors, barriers and facilitators, and women's knowledge and awareness of CBB. The survey captured demographic information (n = 11), including age, race, self-identification as Hispanic or Latino, socioeconomic information (such as household income, health insurance status, and educational attainment), marital status, family history of cancer, and number of children in the household.…”
Section: Survey Instrumentmentioning
confidence: 99%